Regulating the oxidative assisted pyrolysis of Huadian oil shale by preheating temperature and oxygen flow rate. (1st January 2023) - Xu, Shaotao; Sun, Youhong; Guo, Wei; Yang, Qinchuan; Li, Qiang; Guo, Mingyi; Bai, Fengtian; Zhu, Chaofan; Deng, Sunhua
Abstract: The effects of preheating temperature and oxygen flow rate on the reaction behaviour and product yields and characteristics after the oxidative assisted pyrolysis (OP) of Huadian oil shale were systematically investigated in this paper. The results show two marked temperature boundaries in the OP reaction process, namely, the initiation temperature and the ignition temperature. First, an obvious initiation process could be found when the oil shale was preheated above a relatively lower temperature of 190 °C, which was considered to be the first boundary temperature of OP. Actually, the initiation was caused by the self-heating effect which could effectively enhance the pyrolysis of kerogen. Moreover, the self-heating effect could be strengthened by increasing the oxygen flow rate. However, an excessively high preheating temperature or oxygen flow rate may result in excessively high internal temperatures, which could exceed the ignition temperature of some organics, that is, the second boundary temperature of OP. Furthermore, the self-heating effect could improve the contents of heavy components, asphaltenes, and resins in the shale oil products at a suitable preheating temperature. Finally, a mechanism whereby the preheating temperature and oxygen flow rate influence the OP behaviour of oil shale was proposed. Graphical abstract: Image 1 Highlights: There are two boundary temperatures in the OP process of oil shale. The effect of oxygen in OP has three states: ineffective, boost, and consumption. These three states are separated by the two boundary temperatures. The self-heating effect can be effectively enhanced by increasing oxygen flow. The internal temperature of oil shale is a critical factor in the OP process.